Advances in silver nanoparticles: a comprehensive review on their potential as antimicrobial agents and their mechanisms of action elucidated by proteomics - Rodrigues, Adriana S.; Batista, Jorge G. S.; Rodrigues, Murilo Á. V.; Thipe, Velaphi C.; Minarini, Luciene A. R.; Lopes, Patricia S.; Lugão, Ademar B. (Frontiers in Microbiology, 2024)
Nanoparticles play a crucial role in the field of nanotechnology, offering different properties due to their surface area attributed to their small size. Among them, silver nanoparticles (AgNPs) have attracted significant attention due to their antimicrobial properties, with applications that date back from ancient medicinal practices to contemporary commercial products containing ions or silver nanoparticles. AgNPs possess broad-spectrum biocidal potential against bacteria, fungi, viruses, and Mycobacterium, in addition to exhibiting synergistic effects when combined with certain antibiotics. The mechanisms underlying its antimicrobial action include the generation of oxygen-reactive species, damage to DNA, rupture of bacterial cell membranes and inhibition of protein synthesis. Recent studies have highlighted the effectiveness of AgNPs against various clinically relevant bacterial strains through their potential to combat antibiotic-resistant pathogens. This review investigates the proteomic mechanisms by which AgNPs exert their antimicrobial effects, with a special focus on their activity against planktonic bacteria and in biofilms. Furthermore, it discusses the biomedical applications of AgNPs and their potential non-preparation of antibiotic formulations, also addressing the issue of resistance to antibiotics.Silver nanoparticles (AgNPs) are widely described in the literature as having a broad biocidal spectrum, covering Gram-positive and Gram-negative bacteria, fungi, viruses and mycobacteria, in addition to acting synergistically with antibiotics to enhance their effectiveness (Misirli et al., 2021). These properties are based on diverse and complex mechanisms, including the generation of reactive oxygen species (ROS), DNA damage, impairment of bacterial cell membranes and inhibition of protein synthesis (